HUBUNGAN PERHATIAN DARI ORANG TUA TERHADAP HASIL BELAJAR SISWA SD KOTA LUBUKLINGGAU - Pristiana Irza (Primary Education Journal Silampari (PEJS), 2021)
The purpose of carrying out this research is to determine the relationship between parental attention to the learning outcomes of class II SDN 60 Kota Bengkulu Lubuklinggau. Using quantitative correlation. Using a sample of 55 students. Techniques in collecting data using questionnaires and documentation techniques. Techniques in data analysis by applying the formula "Product Moment Correlation" and "Double Correlation". The results of the study showed a significant relationship between parental attention to learning outcomes. This is evidenced by rxy = 0.51542, rxy = 0.26566, t count 3.2944. The conclusion is that: there is a significant relationship between parental attention to the learning outcomes of class II SDN 60 Kota Bengkulu students Keywords: Parents; Family; Learning outcomes; Intelligence; Children's Education